Membangun kesadaran kewarganegaraan di era digital: tantangan dan strategi menuju partisipasi demokratis - Royyani, Mochammad Imdad (Maliki Interdisciplinary Journal, 2025)
The digital era has transformed the landscape of civic life, particularly in terms of citizen participation. The advancement of information technology presents both opportunities and challenges in fostering a critical, active, and responsible sense of citizenship. This paper explores the various obstacles in raising civic awareness amidst the massive flow of digital information, such as disinformation, opinion polarization, and low digital literacy. Furthermore, it outlines strategic approaches to promote democratic participation, including digital-based civic education, the strengthening of media literacy, and the optimization of inclusive virtual public spaces. Using a qualitative approach and literature analysis, this study aims to contribute to the collective effort in developing digitally literate, critical, and democratically engaged citizens in the information age.